Proanthocyanidin trimer gallate modulates lipid deposition and fatty acid desaturation in Caenorhabditis elegans. Issue 11 (31st July 2017) - Nie, Yu; Littleton, Brad; Kavanagh, Thomas; Abbate, Vincenzo; Bansal, Sukhvinder S.; Richards, David; Hylands, Peter; Stürzenbaum, Stephen R.
Abstract : The incidence of obesity is rising at an alarming rate. Despite its recognition as an urgent healthcare concern, obesity remains largely an unsolved medical problem. A comprehensive screen for functional dietary phytochemicals identified proanthocyanidins as putative targets to ameliorate obesity. A full‐scale purification of oligomeric proanthocyanidins (OPCs) derived from grape seed extract yielded pure OPC dimer, trimer, tetramer, and their gallates (pOPCs). Forward chemical screening conducted in Caenorhabditis elegans suggested that pOPCs reduced the activity of lipase in vitro and triglyceride storage capacity in vivo. Proanthocyanidin trimer gallate in particular modified lipid desaturation in C. elegans, revealed by hyperspectral coherent anti‐Stokes Raman scattering microscopy. Exposure to trimer gallate resulted in the transcriptional down‐regulation of nhr‐49 (an ortholog of the human peroxisome proliferator‐activated receptor‐a), and a key regulator of fat metabolism, and 2 downstream genes: fat‐5 and acs‐2. A combination exposure of 2 or 3 pOPCs (dimer gallate, trimer and/or trimer gallate) suggested the absence of synergistic potential. By using the whole‐organism C. elegans coupled with versatile biochemical, biophysical, and genetic tools, we provide an account of the composition and bioactivity of individual OPCs and more generally highlight the potential of traditional Chinese medicine–derived drug leads.—Nie, Y., Littleton, B., Kavanagh, T., Abbate, V., Bansal, S. S., Richards, D., Hylands, P., Stürzenbaum, S. R. Proanthocyanidin trimer gallate modulates lipid deposition and fatty acid desaturation in Caenorhabditis elegans. FASEB J. 31, 4891–4902 (2017). www.fasebj.org